Belvoir, study of the interior castle - Baud, Anne (2023)
The architectural study of the inner castle of Belvoir revealed a construction site that was built from the outer wall. The stones used came from local quarries. Although only the ground floor of the fortification remains, it is possible to reconstruct part of the first floor and more specifically the location of the chapel. The castle was built quickly and several retouches are clearly visible, showing an evolving architectural project. Two elements have been identified on the ground floor: the small cistern dug in the inner courtyard, connected to the large cistern in the outer enclosure, and the room reserved for the ovens, kitchen or sugar refinery.   Bibliographical references         BAUD, Anne; D’AGOSTINO, Laurent– “Le château de Belvoir (Galilée): l’utilisation des agrafes en métal dans la maçonnerie au XIIIe siècle”. In BAUD, Anne; CHARPENTIER, Gérard (dir.) – Chantier et matériaux de construction en Orient et en Occident: actes du colloque tenu au château de Guédelon, 23-25 septembre 2015. Lyon: MOM éditions, 2020, pp. 111-127. ELLENBLUM, Ronnie – Twelfth-Century Buildings in Palestine: A Study ot the Crusader’s Methods of Construction. Jerusalem: The Hebrew University of Jérusalem, 1986. Master thesis. EYDOUX, Henri-Paul – Les châteaux du soleil, Forteresses et guerres des Croisées. Paris: Librairie académique Perrin, 1982. MESQUI, Jean – Châteaux d’Orient. Liban. Syrie. Paris: Hazan, 2001. PRINGLE, Denys – “Some Approaches to the Study of Crusader Masonry Mark in Palestine”. Levant 13 (1981), pp. 173-199. STEM, Eliezer – “La commanderie de l'Ordre des Hospitaliers à Acre”. Bulletin Monumental 164 (2006): L'architecture en Terre Sainte au temps de Saint Louis, pp. 53-60.